2021
DOI: 10.12659/ajcr.932381
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Abolition of Antegrade and Retrograde Conduction in Wolff-Parkinson-White Syndrome: A Case Series

Abstract: Case series Patients: Male, 15-year-old • Female, 19-year-old Final Diagnosis: Wolff-Parkinson-White (WPW) syndrome Symptoms: Palpitation Medication: — Clinical Procedure: — Specialty: Anatomy • Cardiology Objective: Unknown etiology Background: Radiofrequency ablation in cases of Wolff-Parkinson-White (WPW) syndrome is a relatively safe procedure that yields good results. However, the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Sawasaki et al reported two patients that required sequential ablations to achieve anterograde and retrograde conduction across a left lateral pathway and hypothesized that the initial ablation led to an incomplete lesion and a functional block in one direction. However, sequential ablations were in the same location or in the immediate vicinity of each other in their cases 18 . The patients we reported required sequential ablations in two separate anatomic locations making an incomplete lesion an unlikely explanation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Sawasaki et al reported two patients that required sequential ablations to achieve anterograde and retrograde conduction across a left lateral pathway and hypothesized that the initial ablation led to an incomplete lesion and a functional block in one direction. However, sequential ablations were in the same location or in the immediate vicinity of each other in their cases 18 . The patients we reported required sequential ablations in two separate anatomic locations making an incomplete lesion an unlikely explanation.…”
Section: Discussionmentioning
confidence: 78%
“…However, sequential ablations were in the same location or in the immediate vicinity of each other in their cases. 18 The patients we reported required sequential ablations in two separate anatomic locations making an incomplete lesion an unlikely explanation.…”
Section: Discussionmentioning
confidence: 90%